2019
DOI: 10.1590/0034-7167-2018-0366
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy of adults with and without arterial hypertension

Abstract: Objective: Assess the level of health literacy of adults, with and without hypertension, treated in three basic health units (UBS) in Picos, Piauí. Methods: Cross-sectional study conducted with 357 adults. Data were collected using a questionnaire with sociodemographic variables, and literacy was assessed by the Test of Functional Literacy in Adults. Descriptive analysis was performed followed by the association between literacy and exposure variables with Pearson's chi-squared (X²) test and Mann-Whitney U tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
2
16

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 29 publications
3
19
2
16
Order By: Relevance
“…The sociodemographic characteristics found in this study, such as the predominance of females, living with a partner, having more than four years of study, not having a paid job, being white and having an income higher than a minimum wage, were similar to other studies who assessed the FHL (9,21) . In addition, corroborating the research findings, studies that assessed the FHL of people with hypertension also found inadequate or marginal FHL in most investigated participants, as in a study conducted nationwide, in the city of Picos-PI, and internationally, in Isfahan Province, Iran (9)(10) . Education was shown to be linked to FHL, so that older adult with up to 4 years of study had lower averages in the FHL score than those who studied more than 4 years.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…The sociodemographic characteristics found in this study, such as the predominance of females, living with a partner, having more than four years of study, not having a paid job, being white and having an income higher than a minimum wage, were similar to other studies who assessed the FHL (9,21) . In addition, corroborating the research findings, studies that assessed the FHL of people with hypertension also found inadequate or marginal FHL in most investigated participants, as in a study conducted nationwide, in the city of Picos-PI, and internationally, in Isfahan Province, Iran (9)(10) . Education was shown to be linked to FHL, so that older adult with up to 4 years of study had lower averages in the FHL score than those who studied more than 4 years.…”
Section: Discussionsupporting
confidence: 84%
“…A study carried out in Picos-PI found that people with hypertension who had marginal/inadequate FHL had a higher average age than those with adequate FHL (9) . Regarding the older adults, it is important for the professionals to know about the peculiarities of the aging process, its impact on old age, in addition to being able to guide older adults and their relatives in care, aiming at maintaining health and improving well-being from that population.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations